Tung oil-based phosphorus-containing polyol as a flame retardant for bamboo. (22nd February 2023) - Wang, Zhongwei; Yang, Shoulu; Liu, Zhu; Ding, Fangjun; Ji, Ning; Wu, Yiqiang
Highlights: Novel Tung oil-based phosphorus-containing polyol flame retardant (MTTO) was synthesized. Both MTTO and MTTO-coated melamine-modified bamboo confers great flame-retardant and smoke-suppression properties on bamboo. The fire performance mechanism of the MTTO and MTTO-coated melamine-modified bamboo was proposed. Abstract: A novel method for preparing a tung oil-based flame retardant polyol (MTTO) is described. An epoxidized tung oil methyl ester was initially prepared using green nontoxic phosphotungstate (Ag3 O40 PW12 ·xH2 O) as the catalyst. The MTTO was then produced from epoxidized transesterified tung oil (ETOME) using diethyl phosphate and ring-opening. The MTTO molecular structure was analyzed using FTIR, 1 H, 31 P, 13 C NMR, and HR-MS. Both MTTO and MTTO-coated melamine-modified bamboo showed excellent flame retardation, with a UL-94 rating of V-0, increased LOI from 28.3 % to 36.4 % and 38.7 %, and significant reductions in the PHRR and THR of the untreated bamboo of 42.7 % and 50.6 % and 37.5 % and 42.1 %, respectively. MTTO was effective in both the gas and condensed phases, preventing bamboo degradation through the release of non-flammable small molecules and the formation of a cross-linked phosphorus-oxygen network carbon layer. Moreover, the addition of melamine led to the release of more non-flammable gases, expansion of the char layer, and increased density of the nitrogen-phosphorus-oxygen cross-linked network carbon layer during combustion, resulting in reduced PHRR and THR.